Effect of dietary anthocyanins on the risk factors related to metabolic syndrome: A systematic review and meta-analysis - Junyin Pan; Jingwen Liang; Zhantu Xue; Xin Meng; Liwei Jia (PLoS ONE, 2025)
Objective This meta-analysis aims to systematically investigate whether dietary anthocyanin supplementation can reduce metabolic syndrome (MetS)-related risk factors: abdominal obesity, dyslipidemia (low high-density lipoprotein cholesterol (HDL-C) and hypertriglyceridemia), hypertension, and hyperglycemia by conducting a meta-analysis of randomized controlled trials (RCTs). Methods A systematic search of 5 electronic databases (PubMed, Web of Science, Scopus, Cochrane Library, and Embase) was conducted from inception until April 25, 2024. A total of 1213 studies were identified, of which randomized controlled trials involving subjects with MetS-related factors, comparing dietary anthocyanin supplementation with placebo, and reporting results on anthropometric, physiological, and metabolic markers relevant to this study were selected. Depending on the heterogeneity of the included studies, a fixed-effect model was applied for low heterogeneity (I2 < 50%), whereas a random-effects model was employed when substantial heterogeneity was present (I2 ≥ 50%). The weighted mean difference (WMD) and 95% confidence intervals (CI) were calculated. Results This meta-analysis included 29 randomized controlled trials with 2006 participants. The results showed that dietary anthocyanins significantly improved various lipid and glycemic markers: HDL-C: increased by 0.05 mmol/L (95% CI: 0.01 to 0.10, p = 0.026), LDL-C: decreased by 0.18 mmol/L (95% CI: -0.28 to -0.08, p = 0.000), Triglycerides (TGs): reduced by 0.11 mmol/L (95% CI: -0.20 to -0.02, p = 0.021), Total cholesterol (TC): lowered by 0.34 mmol/L (95% CI: -0.49 to -0.18, p = 0.000), Fasting blood glucose (FBG): reduced by 0.29 mmol/L (95% CI: -0.46 to -0.12, p = 0.001), Glycated hemoglobin (HbA1c): decreased by 0.43% (95% CI: -0.74 to -0.13, p = 0.005). Weight: (WMD: -0.12 kg, 95% CI: -0.45 to 0.21, p = 0.473), Body mass index (BMI): (WMD: -0.12 kg/m2, 95% CI: -0.26 to 0.03, p = 0.12), Overall WC: (WMD: 0.18 cm, 95% CI: -0.51 to 0.87, p = 0.613), Systolic blood pressure (SBP): (WMD: -0.12 mmHg, 95% CI: -1.06 to 0.82, p = 0.801), Diastolic blood pressure (DBP): (WMD: 0.61 mmHg, 95% CI: -0.03 to 1.25, p = 0.061), Insulin levels: (WMD: -0.02 mU/L, 95% CI: -0.44 to 0.40, p = 0.932), HOMA-IR: (WMD: -0.11, 95% CI: -0.51 to 0.28, p = 0.573). Additionally, a 100 mg/day dosage of anthocyanins significantly reduced: Waist circumference (WC): by 0.55 cm (95% CI: -1.09 to -0.01, p = 0.047). Subgroup analyses based on intervention duration, anthocyanin dosage, health status, formulation, dosage frequency, physical activity levels, and baseline levels of corresponding markers revealed varying significances, particularly in relation to blood pressure. Conclusion Dietary anthocyanins effectively improve low HDL cholesterol, hypertriglyceridemia, and hyperglycemia, making them a promising adjunct for managing MetS. However, it is important to note that dietary anthocyanin interventions may raise systolic blood pressure (SBP) and diastolic blood pressure (DBP) depending on intervention dose, duration, participant health status, and formulation. Clinicians should fully consider these effects when recommending anthocyanin supplementation. Further long-term, well-designed, large-scale clinical trials are needed to draw definitive conclusions.